Differences in biological age of the best U11 and U13 teams in Croatia - Ajman, H.; Tomac, Z. (Journal of Human Sport & Exercise, 2019)
It is well known that among the individuals who are chronologically at the same age there are individuals who develop below the average as well as those above the average. The data on the level of biological development, are very important for the young athletes in sports. The aim of this research was to determine differences in biological age between male soccer players in the category U11 and U13 of the two best Croatian teams in the year 2011. The estimate for biological age was conducted by a validated questionnaire developed by the authors from the United Kingdom. Gender-specific, pubertal development self-assessment questionnaires were used photographs of the Tanner standards. For all participants anthropometrical characteristics (height, weight and BMI) were determined. For all samples descriptive parameters were calculated and Mann- Whitney U test was used to determine differences. Statistically significant differences weren`t determined in morphological variables. Statistically significant differences were determined only in U11 category in Tanner 1. side standards (U=27,50; p=0.00), and in 2. side (U=41,50; p=0,01) but not in the U13 category (p=0.40). Statistically significant differences were determined in U11 category and maybe at this age that was a factor who had a significant impact on the final result of the championship.